2000
DOI: 10.1038/eye.2000.232
|View full text |Cite
|
Sign up to set email alerts
|

Visual outcome after silicone oil removal and recurrent retinal detachment repair

Abstract: Results Sixty-two eyes were entered into the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1
7

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 12 publications
3
32
1
7
Order By: Relevance
“…Final anatomic success was achieved in all patients. Our rate of anatomic success is higher than that reported in the literature [6, 12, 13]. This observation may be related to refined surgical techniques and better equipments in recent years, e.g.…”
Section: Discussioncontrasting
confidence: 56%
“…Final anatomic success was achieved in all patients. Our rate of anatomic success is higher than that reported in the literature [6, 12, 13]. This observation may be related to refined surgical techniques and better equipments in recent years, e.g.…”
Section: Discussioncontrasting
confidence: 56%
“…3, 4, 6, 8), which persisted after Densiron removal in three (nos. 3,6,8). In all eyes the increased IOP could be treated sufficiently with topical and/or temporary oral administration of anti-glaucoma medication.…”
Section: Anatomical Resultsmentioning
confidence: 98%
“…Jonas et al found that 93.4% ( 185 out of 198) patients with a secondary increase in IOP after silicone oil endotamponade had normalization of IOP after removal of the oil [24]. Flaxel et al reported that elevated IOP persisted in all eyes (62 eyes) after silicone oil removal [89].…”
Section: Silicone Oil Removalmentioning
confidence: 97%